Clinicopathological characteristics and prognosis of brain metastases in elderly patients with esophageal carcinoma - Yi Wang (Wiley, 2021)
Abstract Background Brain metastases (BM) from esophageal carcinoma (EC) is clinically rare and has not yet been reported in elderly patients. This study aimed to investigate the clinicopathological characteristics, outcomes and prognostic factors of BM in elderly patients with EC, in order to provide guidance for clinical practice. Methods A total of 20 EC patients older than 65 years who were diagnosed with BM were identified from the fourth Hospital of Hebei Medical University between January 1, 2009 and December 31, 2018. Survival was evaluated by the Kaplan–Meier method and Cox proportional hazards models. Results The median time from diagnosis of EC to BM was 11.8 months (0–249.2 months). The median overall survival (OS) was 4.8 months (1.13–23.3 months), with 20% of patients achieving the 1‐year survival rate. Patients with KPS score of ≥70 had a significantly better OS than those with KPS score<70 (8.4 vs. 3.9 months, p = 0.033). Compared to patients without brain radiotherapy, patients with brain radiotherapy showed better outcomes in both median OS (8.4 vs. 2.9 months) and 1‐year survival rate (23.1% vs. 14.3%, p = 0.043). The median OS of patients with radiotherapy combined with chemotherapy and/or targeted therapy and radiotherapy alone was 9.7 months (3.4–23.3 months) and 7.2 months (1.7–18.4 months), respectively, with no significant difference between the two groups (p = 0.215). Conclusions Brain radiotherapy provided clinically meaningful survival benefit for elderly patients with BM from EC. Thus, active treatments for those patients might be required.